The Importance of Autogenic Relaxation in Reducing Anxiety Levels for Pregnant Women - Nesi Novita; Suprida (Yayasan Rumah Ilmu Professor, 2022)
Abstract – Anxiety is one of the causes of prolonged labor and fetal death. Autogenic relaxation is a non-pharmacological method for treating anxiety in pregnant women. The purpose of this study was to determine the effect of autogenic relaxation techniques on cortisol levels in third trimester pregnant women. The research was conducted at Pembina Public Health Center in Palembang City with a total sample of 21 people with one group pretest and posttest designThe anxiety level measuring instrument used isHARS scale (Hamilton Anxiety Rating Scale). And measuring cortisol levels using a biomarker examination. And the statistical analysis used in this study is the Wilcoxon test. The results of statistical analysis showed that the mean cortisol level before the intervention was 1.434. And after the intervention was 1.367. And there are differences in the anxiety of pregnant women before and after autogenic therapy with p = 0.001. And there is no correlation between cortisol levels before and cortisol levels after autogenic relaxation p = 0.138.